Investigating the impact of the strength of supply chain integration on cost and responsiveness. Issue 1 (2nd January 2023) - Bae, Hee-sung; Grant, David B.; Banomyong, Ruth; Varadejsatitwong, Paitoon
ABSTRACT : The purpose of this paper is to investigate strength of supply chain integration based on social exchange theory and its resultant impact on supply chain cost and responsiveness. The study surveyed Korean export firms and obtained 182 usable responses. Data were analysed using cluster analysis and analysis of variance. Findings confirm that the strength of supply chain integration provides a mechanism for measuring the width of integration for both suppliers and customers. Further, identifiable gaps in cost performance and responsiveness were found based on strength of supply chain integration. This paper contributes through the development and testing of a conceptual model based on social exchange theory and also offers managerial suggestions in the understanding of customer needs and the importance of sharing information with suppliers in achieving improved cost performance and responsiveness in the supply chain.